2016
DOI: 10.1167/16.11.28
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of visual uncertainty and contextual guidance on perceptual decisions: Evidence from eye and mouse tracking in visual search

Abstract: Visual search can be seen as a decision-making process that aims to assess whether a target is present or absent from a scene. In this perspective, eye movements collect evidence related to target detection and verification to guide the decision. We investigated whether, in real-world scenes, target detection and verification are differentially recruited in the decision-making process in the presence of prior information (expectations about target location) and perceptual uncertainty (noise). We used a mouse-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 87 publications
(123 reference statements)
0
14
0
Order By: Relevance
“…A larger area indicates a more curved line, suggesting greater uncertainty than a smaller area, or more direct line from start to picture selection. Mean AUC provided information about the participants' degree of attraction to the unselected alternative (Freeman & Ambady, 2010;Quétard et al, 2016). A higher AUC measurement suggested that mouse behavior was driven toward the alternate before ultimately making a selection.…”
Section: Discussionmentioning
confidence: 99%
“…A larger area indicates a more curved line, suggesting greater uncertainty than a smaller area, or more direct line from start to picture selection. Mean AUC provided information about the participants' degree of attraction to the unselected alternative (Freeman & Ambady, 2010;Quétard et al, 2016). A higher AUC measurement suggested that mouse behavior was driven toward the alternate before ultimately making a selection.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical significance of the effects was assessed using mixed effects-models (Baayen et al, 2008; Bates et al, 2015; R Core Team, 2014) because they are able to account for between-subject differences, which are unrelated to the task design/experimental manipulation. Additionally, such approach represents a gold standard analysis when dealing with mouse kinematics data to account for participants’ basic motor properties (e.g., a subject can show higher trajectories’ curvature or can be faster/slower compared to another, independently from the decision itself) and was also employed in many previous mouse-tracking studies (Barca & Pezzulo, 2012; Calluso et al, 2018, 2019, 2020; O’Hora et al, 2013a, 2016; Quétard et al, 2016; Quinton et al, 2013; Tabatabaeian et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…During the experiment, eye fixations on the upper screen were recorded with a remote SMI RED eye tracker (SensoMotoric Instruments GmbH, Germany) at a 60 Hz sampling rate. For all eye movement analyses, the detection threshold that defined a fixation was set to 80 ms (Causse et al, 2016;Quétard et al, 2016;Salvucci and Goldberg, 2000). Eight areas of interest (AOIs) were defined, one for each parameter (red rectangles around the parameters in Fig.…”
Section: Eye-tracking Measurementsmentioning
confidence: 99%